2003
DOI: 10.1007/s10162-002-2047-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulus Level on Speech Perception with Cochlear Prostheses

Abstract: This study is one of a series that examines stimulus features important for cochlear implant function. Here, we examine effects of stimulus level. In subjects with cochlear implants, a number of psychophysical tests of temporal discrimination (pulse rate discrimination, gap detection, etc.) show marked improvement as a function of stimulus level through most or all of the dynamic range, while electrode-place discrimination can improve or degrade as a function of level. In this study, effects of these combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
(14 reference statements)
2
17
0
Order By: Relevance
“…The impact of varying the T-level below or above hearing threshold has been investigated in several studies (Skinner et al 1999;Zeng & Galvin 1999;Franck et al 2003;Spahr & Dorman 2005;Boyd 2006;Dawson et al 2007;Zhou & Pfingst 2014;Boyle & Moore 2015). However, as the signal processing differs across different CI devices (Vaerenberg et al 2014), the impact of these different T-level settings cannot be easily generalized from one device to another.…”
Section: Introductionmentioning
confidence: 97%
“…The impact of varying the T-level below or above hearing threshold has been investigated in several studies (Skinner et al 1999;Zeng & Galvin 1999;Franck et al 2003;Spahr & Dorman 2005;Boyd 2006;Dawson et al 2007;Zhou & Pfingst 2014;Boyle & Moore 2015). However, as the signal processing differs across different CI devices (Vaerenberg et al 2014), the impact of these different T-level settings cannot be easily generalized from one device to another.…”
Section: Introductionmentioning
confidence: 97%
“…In the study reported here, we examined suprathreshold measures: maximum comfortable loudness levels (C levels) and dynamic ranges (DRs). Because most speech information delivered by cochlear implants is at suprathreshold levels and speech recognition generally improves as a function of level [Franck et al, 2002], we reasoned that psychophysical responses to suprathreshold stimuli might be more strongly correlated with speech recognition than measures taken just at the threshold level.…”
Section: Introductionmentioning
confidence: 99%
“…-Better results might be obtained by decreasing the dynamic range [18]. -Only using a subset of electrodes might improve speech recognition [42].…”
Section: Description Of the Problemmentioning
confidence: 99%